The impact of product innovation capabilities on the marketing performance of Pontianak's typical food MSMEs with social media marketing as a mediator - Felix Reynard; Lie Heng (Economic: Journal Economic and Business, 2026)
This study aims to analyze the influence of product innovation and social media utilization on the marketing performance of Pontianak's traditional food MSMEs. This study uses a quantitative approach with a causality method and involves 125 respondents of snack food MSMEs determined by the Slovin formula from a population of 234 MSMEs. Data were obtained through questionnaires and analyzed using AMOS software. The results show that product innovation has a positive and significant effect on social media marketing and marketing performance. Social media marketing is also proven to have a positive effect on marketing performance and acts as a mediating variable in the relationship between product innovation and marketing performance of Pontianak's traditional food MSMEs. This study contributes by providing a new perspective regarding the digital marketing strategy of local traditional food MSMEs. The limitations of this study lie in the scope that only covers Pontianak's typical snack MSMEs and the use of a quantitative approach. The research findings provide practical implications for business actors to increase competitiveness through sustainable product innovation and optimal use of social media, as well as serve as a reference for the government in developing MSME digitalization assistance programs.